Unusual shear induced unconventional 1¯011 twinning in Mg. (15th April 2020) - Ma, Shao-Lin; Tang, Xiao-Zhi; Zu, Qun; Guo, Ya-Fang
Abstract: Conventional ( 1 ¯ 011 ) twinning in hexagonal metals has the twin plane K 1 = ( 1 ¯ 011 ) and the corresponding twinning direction η 1 = [ 1 ¯ 01 2 ¯ ] . Twinning shear is generally accomplished through the gliding of two-layer and/or four-layer twinning dislocations (TDs) along η 1 associated with atomic shuffles. Using molecular dynamics simulations, we reveal that an unusual shear along − η 1 associated with atomic shuffles on the twin plane K 1 is resulted by gliding of a one-layer TD. Correspondingly, an unconventional 1 ¯ 011 twinning occurs through successive gliding of one-layer TDs. Such a twinning mechanism is found to be correlated to high stress/strain concentration, such as at crack tip. Graphical abstract: Image, graphical abstract